Analysis of primary care in five municipalities of western amazonia, with emphasis on Family Health Program - Vieira, Janete Maria Rebelo; Garnelo, Luíza; Hortale, Virginia Alonso (Saúde e Sociedade, 2010)
The objective of this paper was to analyze the primary healthcare management process, including the Programa Saúde da Família (PSF - Family Health Program), in five municipalities located in the western part of the Amazon region. Decentralization, understood as a means of improving the local management, was also investigated. This was a qualitative study that explored the political-institutional level of the municipalities' healthcare systems through the dimensions of government project, government capacity and governability. Data collection was accomplished by means of combined techniques: analysis of official documentation from the municipal healthcare systems; conduction of semi-structured interviews with municipal healthcare managers, managers of the primary healthcare services, of PSF and of the administration of healthcare units (both PSF and non-PSF) to subsidize a study on the healthcare provision and management model; and consultation of the national and municipal information systems. The results showed low management capacity, difficulty in defining healthcare priorities, nonexistent or incipient intersectoral actions, limited financial autonomy and a precarious political support base; limited technical training of managers and their team; insufficient and low-qualified technical staff of the services network, which prevent them from performing a skilled management of primary healthcare.